LEGAL CERTAINTY OF SELLER'S PAYMENT RIGHTS IN MARKETPLACE ESCROW SYSTEMS: A NORMATIVE STUDY OF CONTRACTUAL OBLIGATIONS WITHIN ELECTRONIC CONTRACTS - Faris Danuarta; Sarikun; Kamaluddin; Syamsudin (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The development of digital commerce through marketplace platforms has given rise to an escrow system, which places the platform in temporary control of payments in sales transactions. Normatively, the legal relationship of sales and purchases is subject to Article 1457 of the Civil Code, while the legal requirements of an agreement are regulated by Article 1320 and the principle of pacta sunt servanda in Article 1338 of the Civil Code. Electronic contracts as the basis of the relationship between the parties are recognized in Article 18 of the Electronic Information and Transactions Law. This study aims to analyze the legal certainty of the seller's payment rights in the escrow system and the balance of the parties' contractual rights and obligations. This study is a normative legal study with a statutory and conceptual approach. The results show that the escrow system is valid as long as it is regulated in an electronic contract that meets legal requirements. However, legally, the seller's payment rights arise when the buyer fulfills the payment obligation, while escrow only functions as an administrative mechanism. The unclear time limit for holding funds has the potential to create legal uncertainty and contractual imbalance. Therefore, it is necessary to strengthen regulations and interpretations based on the principles of proportionality, good faith, and legal certainty so that protection for sellers in the marketplace ecosystem can be guaranteed fairly.